One Alpha-hydroxycholecalciferol Improves Growth Performance, Tibia Quality, and Meat Color of Broilers Fed Calcium- and Phosphorus-Deficient Diets - Han, J. C. (Asian-Australasian Association of Animal Production Societies (AAAP) and Korean Society of Animal Science and Technology (KSAST), 2012)
An experiment was conducted to evaluate the effects of one alpha-hydroxycholecalciferol (1α-OH D(3)) on growth performance, tibia quality, and skin and meat color in broilers fed calcium (Ca)- and phosphorus (P)-deficient corn-soybean meal diets. A total of 288 male Ross broilers, at 21 days of age, were randomly assigned to three treatments with eight cages per treatment. Three levels of 1α-OH D(3) (0, 5, and 10 μg/kg) were added to a basal diet (0.50% Ca, 0.13% non-phytate phosphorus (NPP), and 0.35% total phosphorus (tP)) without vitamin D(3). As a result of this study, the addition of 1α-OH D(3) increased body weight gain (p<0.001), feed intake (p = 0.007), feed efficiency (p<0.001), tibia weight (p = 0.002), length (p<0.001), breaking-strength (p = 0.012), ash (p<0.001), Ca (p<0.001), and P content (p = 0.004). Dietary 1α-OH D(3) enhanced breast meat yellowness (p = 0.015) and the length and weight of the small intestine of the broilers. Moreover, 1α-OH D(3) decreased serum Ca concentration (p = 0.074) and breast meat redness (p = 0.010). These results indicate that the 1α-OH D(3) improves growth, tibia quality, and meat color in broilers fed Ca- and P-deficient corn-soybean meal diets.